2016
DOI: 10.4168/aair.2015.8.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Method for Primary Nasal Epithelial Cell Culture Using Intranasal Brushing and Feasibility for the Study of Epithelial Functions in Allergic Rhinitis

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Purpose: Although differentiated normal human nasal epithelial (NHNE) cells can be used to study the role of human nasal epithelium, there is a need for effective culture models of nasal epithelium in sinonasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The brush is immediately placed in a 5 mL polystyrene plastic tube containing 5 mL of PBS and cut‐off just above the bristles. The brush will be shaken vigorously in the solution and carefully brushed off against the wall of the tube . The tubes are centrifuged at 400 g for 10 minutes.…”
Section: Nasal Samplingmentioning
confidence: 99%
“…The brush is immediately placed in a 5 mL polystyrene plastic tube containing 5 mL of PBS and cut‐off just above the bristles. The brush will be shaken vigorously in the solution and carefully brushed off against the wall of the tube . The tubes are centrifuged at 400 g for 10 minutes.…”
Section: Nasal Samplingmentioning
confidence: 99%
“…We found that cultured ARNE cells containing the histologic characteristics of allergic rhinitis nasal epithelium during the process of primary cell culture would be useful to investigate the susceptibility of allergic nasal mucosa to IAV infection. 21 The current findings showed that IAV-infected ARNE cells showed significant differences in viral loads, such as higher mRNA levels in cell lysate and viral titres in supernatant compared to IAV-infected NHNE cells. Furthermore, our clinical data showed that influenza-related symptoms such as fever, cough and throat pain in H1N1-positive individuals diagnosed with AR lasted longer and required hospitalization and intensive care.…”
Section: Discussionmentioning
confidence: 47%
“…Cells were cultured in a 1:1 mixture of basal epithelial growth medium and DMEM containing previously described supplements. 9,21 Cultures were grown while submerged for the first 9 days. The…”
Section: Cell Culturementioning
confidence: 99%
“…From January 2013 to January 2015, a total of 142 AR patients were selected from Shanghai Ninth People's Hospital, Shanghai JiaoTong University School of Medicine as a case group. All the patients completed the following tests and questionnaires based on the World Health Organization (WHO) diagnostic criterion of ARIA 2007: anterior rhinoscopy, allergen skin test, history of allergic rhinitis, family history of allergy, and history of food and drug allergies . The inclusion criteria were as follows: (1) age from 15 to 60 years; (2) AR confirmed through skin prick or sensitinogen (fungi, mites and food‐allergens like fish, shrimp and crab) screening test; and (3) no antihistamine agent used in the 2 weeks prior to treatment.…”
Section: Methodsmentioning
confidence: 99%